ANALYSIS OF HAJJ SERVICES FOR THE ELDERLY IN BENGKULU CITY - Jannah, Syifaul; Aziz Zulhakim, Abdul; Pratikno Ramadhan, Adityo (Institut Agama Islam Negeri Metro, 2025)
This study aims to analyze the implementation of elderly-friendly Hajj services in Bengkulu City, Indonesia, where in 2023, out of 1,636 prospective pilgrims, 780 (48%) of them are elderly, of which 312 are from Bengkulu City. This research uses a qualitative descriptive method using Zeithaml's service quality framework which includes five dimensions namely tangible, reliability, responsiveness, assurance, and empathy. Data were collected through observation, interviews, and document analysis with eight key informants selected by purposive sampling, namely six elderly pilgrims from the 2023 Hajj season and two Hajj officers from Bengkulu City. This research uses content analysis through the stages of reduction, presentation, and conclusion. The research findings show that while the accommodation facilities are generally adequate with features such as proper toilet seats and regular maintenance, they still face challenges with the limited availability of toilets suitable for the elderly. The reliability dimension showed strength through the implementation of a comprehensive staff training program and 24-hour support. However, the empathy dimension shows glaring gaps, especially in terms of the lack of staff initiative in providing personalized attention to elderly congregants, except in high-risk cases. The study concludes that while the framework for elderly-friendly Hajj services is in place, its implementation requires better integration of service quality principles, especially in the areas of physical infrastructure and empathic service provision. Key recommendations include improving the accessibility of public facilities through coordination with Saudi Arabian authorities and the establishment of special elderly service teams at the central, provincial, and district/city levels.